General technical knowledge in the vocational training of future workers in vocational schools - Hevko, Ihor Vasilievich (Journal of Education, Health and Sport, 2018)
The article considers methodological provisions for the unification of educational material on technology in vocational schools. It is proved that one of the effective ways to increase the level of knowledge of students is the grouping of professions on the basis of general educational technical training. It was determined that insufficient attention was paid to the issues of training workers for groups of related professions.